Irrigation schemes in Ethiopia’s Awash River Basin: An examination of physical, knowledge, and governance infrastructures - Mekonnen, Dawit Kelemework; Yimam, Seid; Arega, Tiruwork; Alemu, Tekie; Gonfa, Kidist H.; Ringler, Claudia (International Food Policy Research Institute, 2024)
Using a representative sample of irrigation schemes, the study documents the physical, knowledge, and governance infrastructures of irrigation schemes in Ethiopia’s most intensively used river basin, the Awash. The findings show that about 20 percent of the equipped area of irrigation schemes in the basin is not being irrigated, while the number of actual beneficiaries on average exceeds the number of planned beneficiaries. The results also show significant knowledge gaps among irrigation scheme managers, extension agents, and leaders of water users’ associations (WUAs): 96 percent of them do not know the total water withdrawals or the irrigation water requirement per season. About 14 percent of the surveyed irrigation schemes have neither traditional water committees nor WUAs, and only 21 percent are organized in legally registered WUAs despite a substantial number of identified benefits of these organizations. Moreover, only 58 out of 489 irrigation schemes have women committee members. Many schemes lack a clear strategy for covering maintenance costs: almost 40 percent of schemes collect contributions from members only when the system fails, while 17 percent report no contributions for maintenance at all suggesting considerable risk of system deterioration and failure. The results challenge some of the assumptions about irrigation infrastructure in Ethiopia and confirm and quantify other assumptions in the literature.